FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA - Lisma Lismawati, SE. M.Si. Ak. CA; Munawaroh Munawaroh (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
This study aimed to examine the effect of underwriter’s reputation, corporate profitability (ROA), financial leverage (DER), firm’s scale and firm’s age on the level of underpricing. This study uses 36 companies which run IPOs in Indonesia Stock Exchange in the period of 2009-2013 as its samples. Secondary datas were used and obtained from the Indonesian Stock Exchange by using multiple regression analysis testing to prove the research’s hypothesis. The results shows that the underwriter's reputation and firm’s age do not significantly affected the level of underpricing. Corporate profitability (ROA) affected the underpricing negatively, financial leverage (DER) affected on the level of underpricing positively and the scale of companies underpricing affected negatively on the level of underpricing.